Abstinence‐Related Word Associations and Definitions of Abstinence and Virginity Among Missouri High School Freshmen. (21st October 2013) - Wilson, Kelly L.; Smith, Matthew Lee; Menn, Mindy
ABSTRACT: BACKGROUND: The ways in which adolescents define and view sex, abstinence, and virginity impact the efforts of sexuality educators and sexual health professionals. This study examined terminology used by nonsexually active high school students to define abstinence and virginity and identified words students associate with these terms. Purposes included (1) describing words/phrases associated with abstinence; (2) describing phrases for "being abstinent until marriage" and "being a virgin;" (3) assessing concordance between word dyads associated with abstinence; and (4) assessing concordance between phrases defining "abstinent until marriage" and "a virgin." METHODS: In this study, 216 freshmen provided information about beliefs, behaviors, and perceptions. Pearson chi‐square tests and Wilcoxon sign‐rank tests assessed sex‐based differences, definitions, and levels of concordance were conducted. RESULTS: Girls' friends took an abstinence pledge (p = .004) and their parents (p = .025) and best friends (p < .001) think they should abstain. Male counterparts reported being dissatisfied with current sex status (p = .002) and high acceptance of sex before marriage (p = .011). Boys were more likely to endorse "negative" words than girls. CONCLUSIONS: Professionals need to use relevant materials incorporating terminology that resonates with adolescents and programs that engage coherent participant discussions.